Information Theory over Multisets - Bonchis, Cosmin; Izbasa, Cornel; Ciobanu, Gabriel (Computing and Informatics, 2012)
Starting from Shannon theory of information, this paper presents the case of producing information in the form of multisets, and encoding information using multisets. We review the entropy rate of a multiset information source and derive a formula for the information content of a multiset. Then we study the encoder and channel part of the system, obtaining some results about multiset encoding length and channel capacity.